INSTITUTIONS AND PUBLIC POLICY FOR INDIA'S SUSTAINABLE DEVELOPMENT - Sukhapal Singh; Jha, Jyotsna; Indira, A.; Arunkumar, A. V. (ROUTLEDGE, 2025)
Sustainable development has emerged as an overarching concern globally. Given the challenges of climate change, national economies, especially in the developing world, face unsustainable levels and patterns of growth and development. This volume looks at how India's sustainable development has progressed through institutional changes and public policy discourse. It studies the three pillars of sustainability - technology, governance, and finance. The authors examine whether institutions have been able to work towards becoming inclusive and participatory and whether public policy can remain relevant and agile in a fast-changing world to ensure sustainable development. Written in honour of Professor Vinod Vyasulu, an erudite economist with wide-ranging interests, this volume will be of interest to academics and practitioners engaged with issues of development, policy, institutions, and technology in the fields of Economics, Sociology, Development Studies, Public Policy, and South Asian Studies.
Keywords: India -- Economic conditions.; Sustainable development.; elektronické knihy; electronic books